Exporting freedom : religious liberty and American power - Su, Anna, 1980- (Cambridge, Massachusetts : Harvard University Press, 2016)
Religious freedom is recognized as a basic human right, guaranteed by nearly all national constitutions. Anna Su charts the rise of religious freedom as an ideal firmly enshrined in international law and shows how America's promotion of the cause of individuals worldwide to freely practice their faith advanced its ascent as a global power. -- From book jacket.
Introduction -- White man's burden -- Removing the fertile sources of war -- A God-fearing democracy -- Spiritual disarmament -- Cold war, hot rights -- Age of exceptionalism -- Conclusion.
Includes bibliographical references (pages 239-270) and index.
1 2
Keywords: Freedom of religion -- United States -- History; Freedom of religion -- History; United States -- Foreign relations; Religion and international relations -- United States -- History; Diplomatic relations; Freedom of religion; Religion and international relations; United States; Religionsfreiheit; Außenpolitik; USA; History